Ability and accuracy of patient-performed blood pressure monitoring among pregnant women in urban GhanaAJOG Global Reports at a Glance - Emma R. Lawrence, MD; Titus K. Beyuo, MD, PhD; Noah Newman, MPH; Makafui Aku Klutse, MD; Joshua Kafui Asempa, MD; Andrea Pangori, MS; Cheryl A. Moyer, PhD; Jody R. Lori, PhD; Samuel A. Oppong, MD (Elsevier, 2023)
BACKGROUND: Patient-performed blood pressure monitoring in pregnancy is rarely performed in low- and middle-income country settings, including Ghana. The clinical efficacy of home blood pressure monitoring relies on a pregnant patient being able to independently execute the correct steps to position and use a blood pressure monitor and to achieve accurate blood pressure measurements. OBJECTIVE: This study aimed to (1) assess whether pregnant women can correctly use an automatic blood pressure monitor to check their blood pressure before and after a brief training and (2) determine whether blood pressure values measured by pregnant women using an automatic monitor are similar to values measured by a healthcare provider using a standard clinic monitor. STUDY DESIGN: This was a cross-sectional study conducted at the Korle Bu Teaching Hospital, a tertiary hospital in Accra, Ghana. Participants were adult pregnant women presenting for their first prenatal care visit. Data collection was performed by 2 Ghanaian physicians. Information on demographics, obstetrical history, and past medical history was collected. A brief training was provided on the correct use of the blood pressure monitor, including a verbal script, annotated photographs, and a hands-on demonstration. Pre- and posttraining assessments using a 9-item checklist of correct preparation, position, and use of an automatic blood pressure monitor were performed. Following a modified British Hypertension Society protocol, a series of 4 blood pressure measurements were taken, alternating between provider performed using a clinic monitor and patient performed using an automatic monitor intended for individual use and validated in pregnancy. RESULTS: Among 176 participants, the mean age was 31.5 years (±5.6), and 130 (73.9%) were multiparous. Regarding socioeconomic characteristics, 128 (72.7%) were married, 171 (97.2%) had public insurance, and 87 (49.7%) had completed ≤9 years of formal education. Regarding clinical blood pressure issues, 19 (10.9%) had a history of a hypertensive disorder in a previous pregnancy, and 6 (3.4%) had chronic hypertension. Before receiving any training, 21 participants (12.1%) performed all 9 steps correctly to prepare, position, and use the automatic blood pressure monitor. Comparing pretraining vs posttraining ability, statistically significant increases were seen in the correct performance of each step and the mean number of steps performed correctly (6.1±1.8 vs 9.0±0.2, respectively; P<.001) and proportion performing all 9 steps correctly (12.1% vs 96.6%, respectively; P<.001). The mean difference between doctor-performed and patient-performed blood pressure measurements was 5.6±4.8 mm Hg for systolic blood pressure values and 3.4±3.08 mm Hg for diastolic blood pressure values, with most differences within 5 mm Hg for both systolic blood pressure values (102/176 [58.0%]) and diastolic blood pressure values (141/176 [80.1%]). CONCLUSION: After a brief training, pregnant women in Ghana demonstrated that they are able to use an automatic blood pressure monitor to check their blood pressure correctly and accurately.